1972
DOI: 10.1021/jo00979a012
|View full text |Cite
|
Sign up to set email alerts
|

Diquaternary salts. I. Preparation and characterization of the diquaternary salts of some diazines and diazoles

Abstract: hydrogen and the -NCX group could be through the orbitals of the C=X bond. However, this formulation leaves unanswered the fact that only HNCO and HNCS are detected in the products, although under the conditions of our analysis, namely, at least 25% decomposition and in a 10-cm ir gas cell, this could be accounted for if the rate constant of isomerization of these species is at least twenty times larger as that for elimination. We plan to do more work along these lines and to extend the investigation to the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 1 publication
3
71
0
1
Order By: Relevance
“…Although the methylation of N-1 proceeds smoothly even at low temperature, alkylation of the tertiary N-3 requires prolonged heating at high temperature for several days, 16 apparently due to reduced nucleophilicity of the N-3 atom. 17 In this communication we describe an effective method to prepare imidazoliums by using trimethyloxonium salts, also known as Meerwein salt 18 , which has been used previously to quaternize a variety of heterocyclic amines. 17, 19 We also report solvent dependent tautomerism of the synthesized compounds and their ability to participate in different reactions.…”
mentioning
confidence: 99%
“…Although the methylation of N-1 proceeds smoothly even at low temperature, alkylation of the tertiary N-3 requires prolonged heating at high temperature for several days, 16 apparently due to reduced nucleophilicity of the N-3 atom. 17 In this communication we describe an effective method to prepare imidazoliums by using trimethyloxonium salts, also known as Meerwein salt 18 , which has been used previously to quaternize a variety of heterocyclic amines. 17, 19 We also report solvent dependent tautomerism of the synthesized compounds and their ability to participate in different reactions.…”
mentioning
confidence: 99%
“…Interestingly, the reaction of 1-methyl-1,2,4-triazole with Me 3 O + BF 4 − under forceful conditions is known to produce 1,2,4-trimethyl-1,2,4-triazolium dications [33]. Preliminary experiments with Me 3 O + BF 4 − in dichloromethane showed that 4-amino-1,2,4-triazole gave mixtures of at least mono-, di-and trimethylated products of not yet fully known constitution.…”
Section: Resultsmentioning
confidence: 99%
“…Methylation with iodomethane occurs at N4; when trimethyloxonium tetrafluoroborate is used as methylating agent, the reaction takes place at both nitrogen atoms, leading to the diquaternary salt 390 (Scheme 14.105) [213]. Reaction of 3-amino-1,2,4-thiadiazole (396) with trimethyloxonium tetrafluoroborate occurs at N2 to yield the thiadiazolium salt, which, on basification, undergoes a Dimroth rearrangement to give the 5-methylamino derivative 397 (Scheme 14.108) [215].…”
Section: 24-thiadiazolidinesmentioning
confidence: 99%